Literature Review : The Effect Of Ginger (Zingiber Officinale Var. Amarum) And Honey On Blood Pressure Reduction - Fifi Luthfiyah; Mita Anggraeni; Retno Wahyuningsih (Journals of Ners Community, 2022)
The prevalence of hypertension in NTB at 2018 was 27.8%, this figure was higher than 2013, which was 24.3%. Hypertension management can be done pharmacologically and non pharmacologically. Non pharmacological therapy can be done by consuming honey and ginger. Honey and ginger contain chemical components that can help lower blood pressure. To conduct a literature study on the effect of ginger (Zingiber officinale var. Amarum) and honey on reducing blood pressure. The literature search in this literature review was carried out using five databases with low to high quality, namely Scopus, ProQuest, Pubmed, Garuda Garba, and Google Schoolar. The keywords used are "ginger and blood pressure", "ginger and diastoleic pressure", "ginger and pulse pressure", "ginger and systolic pressure", "ginger officinale and blood pressure", "ginger officinale and diastoleic pressure", " ginger officinale and pulse pressure "," ginger officinale and systolic pressure "," honey and blood pressure "," honey and diastoleic pressure "," honey and systolic pressure ". From 10 journals that have been reviewed, all states that honey and ginger can reduce blood pressure. Honey was able to lower blood pressure with an average decrease in systolic blood pressure by 5.6 mmHg - 30.00 mmHg and a decrease in the average diastolic blood pressure by 7.3 mmHg - 13.00 mmHg, while ginger was able to lower blood pressure by an average -The decrease in systole was 4.73 mmHg - 7.7 mmHg and the decrease in diastolic blood pressure was 5.7 mmHg - 7.27 mmHg. The average dose of honey given is 30 grams - 70 grams, while the average dose of ginger is 4 grams. Form 10 journals have been reviewed, all journals stated that honey and ginger can lower blood pressure and based on all these journals it is known that honey has a greater effect on reducing blood pressure than ginger.